THE INFLUENCE OF COMPETENCE, WORK MOTIVATION, AND WORK FACILITIES ON EMPLOYEE PERFORMANCE AT QONA’AH HOSPITAL, SAMPANG - Hendry Ariyanto; Asri Asri; Mirrah Samiyah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the influence of competence, work motivation, and work facilities on employee performance at Qona’ah Hospital, Sampang, both partially and simultaneously. The study employed a quantitative approach with a cross-sectional design. Data were collected using a five-point Likert-scale questionnaire and analyzed through multiple linear regression. The population comprised 150 hospital employees, and the sample size was determined using the Slovin formula with a 5% margin of error, yielding 109 respondents selected through simple random sampling. The findings indicate that competence, work motivation, and work facilities jointly have a significant effect on employee performance. Partially, work motivation shows a positive and significant effect on employee performance, while competence and work facilities exhibit positive but non-significant effects within the same model. The Adjusted R² suggests that the model explains only part of the variance in employee performance, implying that other organizational and work-related factors may also contribute. These results highlight the managerial importance of strengthening motivational drivers while maintaining competence as a baseline standard and aligning work facilities more precisely with unit-level workflow needs to support performance in the hospital setting.